Plant pathology and plant pathogens. - Lucas, J. A. (John Alexander), 1948- (Wiley-Blackwell, 2020)
"Plant Pathology is the scientific study of plant diseases and the pathogens that cause them, including viruses, bacteria, fungi, oomycetes and nematodes. The management of plant disease, disease cycles and the environmental conditions associated with disease are also integral to the study of plant pathology. Plant disease is relevant to many areas of biological and agricultural science; for example it has impacts on crop quality and yield, horticulture, plant biodiversity and human health and wellbeing. Some well-known examples of plant pathogens include potato blight (Phytophthora infestans), Fusarium wilt disease (Fusarium spp.) which affects grain and other crops and the recent Ash dieback epidemic (Chalara fraxinea). The need for effective crop protection is now even more pressing with the estimates of population growth and adaptation to more variable climate. The link between fundamental discovery and practical application in crop protection is vital. Like all of biology, plant pathology is now embracing the "Omics revolution", and recent advances in plant breeding and biotechnology are also leading to a better understanding of pathogen biology and plant responses to disease"--